2001
DOI: 10.1029/2001gl013023
|View full text |Cite
|
Sign up to set email alerts
|

Retention of dissolved iron and FeII in an iron induced Southern Ocean phytoplankton bloom

Abstract: Abstract.During

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 25 publications
8
106
0
2
Order By: Relevance
“…In this study and SOIREE (Croot et al, 2001), Fe(II) was still detectable several days after an iron infusion. In SOIREE, limited measurements for Fe(II) in surface waters was made and no vertical profiles were performed, but there Fe(II) was found to be an appreciable fraction of the surface DFe even up to 4 days after the last infusion (Croot et al, 2001) during a period of low wind mixing. In the present study, we found that during the initial part of the study when wind mixing was lowest, Fe(II) was still detectable 7 days after the initial infusion (Fig.…”
Section: Fe(ii) Horizontal Distributionmentioning
confidence: 75%
See 4 more Smart Citations
“…In this study and SOIREE (Croot et al, 2001), Fe(II) was still detectable several days after an iron infusion. In SOIREE, limited measurements for Fe(II) in surface waters was made and no vertical profiles were performed, but there Fe(II) was found to be an appreciable fraction of the surface DFe even up to 4 days after the last infusion (Croot et al, 2001) during a period of low wind mixing. In the present study, we found that during the initial part of the study when wind mixing was lowest, Fe(II) was still detectable 7 days after the initial infusion (Fig.…”
Section: Fe(ii) Horizontal Distributionmentioning
confidence: 75%
“…9). Sunlight, and in particular UV radiation (Rijkenberg et al, in press), may however be a more important mechanism under normal low iron conditions in the open ocean (Croot et al, 2001). …”
Section: Model Resultsmentioning
confidence: 99%
See 3 more Smart Citations